Planta Oryza - Domingo, Joycielle T.; Heje, Martin Christian M.; Manahan, Charisse B.; Quintana, Ma. Jannica Rae S.; Rala, Mira Gail G.; Rodriguez, Ervin Carl E.; Sarita, Aubrey Mar Beth I. and Tabiano, Justin Mae I. 4 0 16; 5
u
Feasibility Study: (Bachelor of Science in Accountancy)- Pamantasan ng Lungsod ng Maynila, 2012.
Keywords: 2 -- 0; 6; 20; 20; 2